2020
DOI: 10.7589/2019-09-219
|View full text |Cite
|
Sign up to set email alerts
|

Ticks Parasitizing the Spur-Thighed Tortoise (Testudo Graeca) Population of Tunisia

Abstract: From March to April 2017, a total of 147 free-ranging spur-thighed tortoises ( Testudo graeca) was captured in different habitat types of northern Tunisia and examined for tick infestation. A total of 134 was infested, yielding an infestation prevalence of 91.2%. From these tortoises, 1,174 ticks were collected, a subsample (10%, n=120) of which was randomly selected and identified; the remaining ticks were stored at −80 C and examined for zoonotic pathogens. Only adult Hyalomma aegyptium were found among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…This suggests that the samples examined had extremely low levels of C. burnetii, which needed a multicopy target to achieve the sensitivity required for detection. The presence of samples that tested positive for IS1111 was completely expected, given that C. burnetii strains might contain up to 110 IS1111 elements [7]. Therefore, our study is consistent with a report from a systematic review on the prevalence of C. burnetii in milk from various regions of Iran, which ranged from 4.22-25.55% [29].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This suggests that the samples examined had extremely low levels of C. burnetii, which needed a multicopy target to achieve the sensitivity required for detection. The presence of samples that tested positive for IS1111 was completely expected, given that C. burnetii strains might contain up to 110 IS1111 elements [7]. Therefore, our study is consistent with a report from a systematic review on the prevalence of C. burnetii in milk from various regions of Iran, which ranged from 4.22-25.55% [29].…”
Section: Discussionsupporting
confidence: 91%
“…Different protocols target multiple plasmids and chromosomal genes. For instance, IS1111, icd, com1, sodB, and GroEL/htpB genes have been employed [7]. The target gene IS1111 is a transposase-like insertion sequence, and the number of copies per genome varies from 7 to 110 between isolates [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ticks were more abundant on males than on females or juveniles (Segura et al 2019). In populations of T. graeca from Tunisia, the prevalence of H. aegyptium was 91.2% during spring (Najjar et al 2020). According to these authors, differences in the intensity of tick infestation were observed based on the size of the tortoises and the vegetation cover; the overall infestation abundance was 8.5 ticks per tortoise.…”
mentioning
confidence: 95%
“…-Tortoises are frequently parasitized by ticks (Ixodidae), which are located mainly on the hind limbs (Brianti et al 2010). Tick infestation is very common on wild specimens of T. graeca from northern Africa, notably Morocco, Algeria, and Tunisia (Segura et al 2019;Najjar et al 2020), and has also been reported in the southeastern Iberian Peninsula, but not in Doñana (Díaz-Paniagua and Andreu 2015). In the Maâmora forest of northwestern Morocco, 92.5% of the tortoises were parasitized by ticks in spring, with an infestation intensity and an abundance of 6.7 and 6.2 ticks per tortoise, with 95.6% of the ticks being Hyalomma aegyptium, present on 100% of the parasitized tortoises).…”
mentioning
confidence: 97%